A modulação da via cAMP / PKA pelo sensor neural de cálcio - 1 independe de receptores de dopamina. - Bruno Rezende de Souza (2007)
Neuronal calcium sensor-1 (NCS-1) is the most ancient protein of EF-hands super family which is a group of proteins that binds calcium. It was shown that NCS-1 has many functions such as its capacity of inhibiting dopamine receptor D 2desensitization and its capacity to activate phosphatidylinositol 4-kinase (PI4K). The dopamine and cAMP regulated phosphoprotein-32kDa (DARPP-32) has a central role in modulation of transduction of dopaminergic signaling. When phosphorylated at Threonine 34, DARPP-32 turns into a potent inhibitor of protein phosphatase-1 (PP-1) and consequently modulates the signaling integration. Recently it was demonstrated upregulation of NCS-1 and DARPP-32 downregulation in prefrontal (PFC) cortex of schizophrenic patients. In our study we have investigated the role of NCS-1 on cAMP/PKA intracellular signaling pathway modulation. We also investigated if chronic treatment with typical and atypical antipsychotics modulates NCS-1 and DARPP-32 expression, both in vitro and in vivo (in rat model). We used pheochromocytome PC12 wild-type cells (WT) and overexpressing NCS-1 (Clone). Our results showed that Clone PC12 cells have reduction in DARPP-32 expression, cAMP levels, pDARPP-32(Thr34) and pCREB(Ser133). However, there was no alteration in D, Calcyon, pDARPP-232(Thr75), Akt and pAkt(Ser473) in these same cells. WT and Clone PC12 cells were treated with specific dopaminergic agonists and antagonists and we show that alteration in pDARPP-32(Thr34) levels in Clone PC12 cells is independent of dopaminergic signaling. Also, we demonstrated that both PC12 cells and different brain regions of rats treated chronically with typical and atypical antipsychotics did not present alteration in NCS-1 and DARPP-32 expression. Therefore, we observed that NCS-1 modulates DARPP-32 expression and cAMP/PKA signaling pathway independently of dopamine.